Dynamics of the structure and regional profile of eye damage in children - L. S. Khamraeva (Российский офтальмологический журнал, 2025)
Purpose: to study the dynamics of the structure and regional profile of eye injuries in children for 2018—2022 based on materials from the Tashkent Medical Institute pediatric ophthalmology department. Material and methods. A retrospective analysis of the situational reporting documentation was carried out according to the leading diagnosis according to the ICD 10 classifier. Results. The analysis showed that every fourth child (27.2%) was h ospitalized with eye injury or its complications. Most often, children aged 5 to 14years (61.0—64.5%) sought help, with boys predominating (62.6%). Children applied from all regions of the republic, most often from Tashkent (47.9—60.1%) and Kashkadarya (10.3—13.3%) regions. The structure of eye injuries and their complications has not changed over 5 years: the leading positions were occupied by penetrating wounds of the eyeball and contusions. Complications included scars and corneal opacities, cataracts, endophthalmitis, and secondary glaucoma. Conclusion. Currently, all age groups of children are vulnerable to injury. This dictates the need for widespread activation of injury prevention, accessible emergency high-tech care, taking into account the identified dynamics of the structure and regional profile of eye injuries in children.